ANIMO DOSEN STPBI DALAM GERAKAN SEMESTA BERENCANA BALI RESIK SAMPAH PLASTIK DI KARANGASEM, BALI - Yoga Kharisma Pradana Gede (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of writing this article is to publish an achievement of community service activities in Karangasem. Generally, the enthusiasm of the STPBI Lecturers is seen in tourism, hospitality, and education events. However, it turns out that there is an interest from STPBI lecturers in the Bali Resik Plastic Waste Planning Universe Movement in Karangasem. The problems are: 1) What is the structure of the Bali Planned Universe Movement for Recycling Plastic Waste in Karangasem? 2) What are the STPBI Lecturers' animo on the Bali Planned Universe Movement to Clean Up Plastic Waste in Karangasem?. The article was completed using a qualitative method. Secondary data was obtained based on a literature study, while primary data was obtained through interviews and participation observations. All data have been analyzed qualitatively. The results show that: 1) The Bali Resik Plastic Waste Planned Universe Movement in Tribuana village, was held in the form of community service activities to clean plastic waste using broom sticks and campil or non-organic garbage bags; and 2) The enthusiasm for duplicating waste disposal methods and following the Bali Resik Plastic Waste Planned Universe Movement from preparation, implementation to completion shows the enthusiasm of the STPBI lecturers.